Encyclopedia of sciences and religions - Runehov, Anne L. C.
"To all who love the God with a 1000 names and respect science” In the last quarter century, the academic field of Science and Theology (Religion) has attracted scholars from a wide variety of disciplines. The question is, which disciplines are attracted and what do these disciplines have to contribute to the debate? In order to answer this question, the encyclopedia maps the (self)-identified disciplines and religious traditions that participate or might come to participate in the Science and Religion debate. This is done by letting each representative of a discipline and tradition answer specific chosen questions. They also need to identify the discipline in relation to the Science and Religion debate. Understandably representatives of several disciplines and traditions answered in the negative to this question. Nevertheless, they can still be important for the debate; indeed, scholars and scientists who work in the field of Science and Theology (Religion) may need knowledge beyond their own specific discipline. Therefore the encyclopedia also includes what are called general entries. Such entries may explain specific theories, methods, and topics. The general aim is to provide a starting point for new lines of inquiry. It is an invitation for fresh perspectives on the possibilities for engagement between and across sciences (again which includes the social and human sciences) and religions and theology. This encyclopedia is a comprehensive reference work for scholars interested in the topic of ‘Science and Religion.’ It covers the widest spectrum possible of academic disciplines and religious traditions worldwide, with the intent of laying bare similarities and differences that naturally emerge within and across disciplines and religions today. The A–Z format throughout affords easy and user-friendly access to relevant information. Additionally, a systematic question-answer format across all Sciences and Religions entries affords efficient identification of specific points of agreement, conflict, and disinterest across and between sciences and religions. The extensive cross-referencing between key words, phrases, and technical language used in the entries facilitates easy searches. We trust that all of the entries have something of value for any interested reader. Anne L.C. Runehov and Lluis Oviedo.
Keywords: Religionswissenschaft